2007
DOI: 10.1016/j.ijsolstr.2007.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Buckling analysis of plain knitted fabric sheets under simple shear in an arbitrary direction

Abstract: Knitting structures make plain knitted fabric different from woven fabric. With the aid of a micro-constitutive model the buckling of a knitted fabric sheet subjected to simple shear in an arbitrary direction is investigated. The large deformation of the fabric sheet in its critical configuration is considered. The theory of stability for finite deformations is applied to the analysis. All the stress boundary conditions of the knitted fabric sheet are satisfied. An equation for determining the buckling directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It was determined that some knitted fabrics may stretch up to four times. 40,41 After extension, the deformed specimen shape was captured by a mirror digital photo camera Pentax K7 (18–55 mm F/3.5–5.6 AL lens). The distance from the specimen to the lens was 500 mm and upper lighting with Epistar 9W LED lamps (color temperature 3000–6000 K) is used.…”
Section: Methodsmentioning
confidence: 99%
“…It was determined that some knitted fabrics may stretch up to four times. 40,41 After extension, the deformed specimen shape was captured by a mirror digital photo camera Pentax K7 (18–55 mm F/3.5–5.6 AL lens). The distance from the specimen to the lens was 500 mm and upper lighting with Epistar 9W LED lamps (color temperature 3000–6000 K) is used.…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al [9] carried out a series of uniaxial and biaxial tensile experiments to determine the mechanical properties of the envelope fabric Uretek3216A and found that the elastic constants should be determined for specific loading conditions due to its significant variation with the experimental protocols. Kilby [10] studied the effect of shear property on the buckling behavior of woven fabrics in both principal directions and more comprehensive researches at a random angle to the thread direction have been proposed by Zhaoqun Du [11] and Zhang et al [12] Additionally, quantities of comparisons between the uniaxial and biaxial tests results on the fabric yarns have been performed. It is accepted by investigators [13,14] that nonlinear biaxial characteristics were hard to be inferred from uniaxial experiments alone.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 However, very few papers on simulations of draping and buckling/wrinkling of knitted fabrics have appeared in the open literature. 20 A plain knitted fabric sheet under tension along a non-course direction can buckle, and one under tension along a course direction cannot buckle. The critical value of shear amount and the buckling direction angle can determine the forms of fabric buckling shapes.…”
mentioning
confidence: 99%